Problems with extracellular recording of electrical activity in gastrointestinal muscle. - Sanders, Kenton M.; Ward, Sean M.; Hennig, Grant W. (Nature Reviews Gastroenterology & Hepatology, 2016)
Motility patterns of the gastrointestinal tract are important for efficient processing of nutrients and waste. Peristalsis and segmentation are based on rhythmic electrical slow waves that generate the phasic contractions fundamental to gastrointestinal motility. Slow waves are generated and propagated actively by interstitial cells of Cajal (ICC), and these events conduct to smooth muscle cells to elicit excitation–contraction coupling. Extracellular electrical recording has been utilized to characterize slow-wave generation and propagation and abnormalities that might be responsible for gastrointestinal motility disorders. Electrode array recording and digital processing are being used to generate data for models of electrical propagation in normal and pathophysiological conditions. Here, we discuss techniques of extracellular recording as applied to gastrointestinal organs and how mechanical artefacts might contaminate these recordings and confound their interpretation. Without rigorous controls for movement, current interpretations of extracellular recordings might ascribe inaccurate behaviours and electrical anomalies to ICC networks and gastrointestinal muscles, bringing into question the findings and validity of models of gastrointestinal electrophysiology developed from these recordings.